2011
DOI: 10.3892/etm.2011.224
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induces the apoptosis of human breast cancer MCF-7 cells through activation of caspase-3 and inhibition of HERG channels

Abstract: Abstract. arsenic trioxide (as 2 O 3 ) has been widely used to treat patients with acute promyelocytic leukemia and has also been shown to exhibit therapeutic effects on various types of solid tumors, including gastric cancer and lung carcinoma. Breast cancer is a type of solid tumor whose incidence has been increasing for many years. the present study was designed to investigate the effects of as 2 O 3 on the human breast cancer cell line mcF-7, and to explore its potential mechanisms. the mtt assay demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Importantly, KCNQ1 also exhibits similar levels of expression to hERG in these three EST profile sets. We also caution that these data may represent a conservative estimate, as some examples of negative expression in the hERG EST profile, such as breast tumors, contradict existing functional evidence in these cells 8,9 .…”
Section: Surveying Herg Gene Expressionmentioning
confidence: 85%
See 1 more Smart Citation
“…Importantly, KCNQ1 also exhibits similar levels of expression to hERG in these three EST profile sets. We also caution that these data may represent a conservative estimate, as some examples of negative expression in the hERG EST profile, such as breast tumors, contradict existing functional evidence in these cells 8,9 .…”
Section: Surveying Herg Gene Expressionmentioning
confidence: 85%
“…This is demonstrated by experiments using MCF-7 breast cancer cells, in which application of the selective inhibitor E4031 has identified a distinct role for hERG in volume regulation that is separate from the proliferation mediated by the closely related human ether-a-go-go gene (hEAG) potassium channel 9 . These proliferative effects are blocked by astemizole 9 , which is known to inhibit both hEAG and hERG, while caspase-3 dependent apoptosis may be initiated by the similarly nonspecific effects of arsenic trioxide 8 . Taken together with previous evidence that associates genetically linked LQTS with mutations in at least eleven genes, including other potassium, calcium, and sodium channels 47,48 , such data suggest that compounded effects on hERG and other ion-conductive proteins might not be easily separated with nonselective modulators.…”
Section: Roles In Cancermentioning
confidence: 99%
“…In the 1970s, Chinese researchers were the first to discover its ability to cure acute promyelocytic leukemia (APL) (4). Since then other research groups have demonstrated worldwide that As 2 O 3 also inhibits the growth of various solid tumors, including esophageal carcinoma (5,6), breast (3,7,8), bladder (9), lung (10) and liver cancer (11), multiple myeloma (12), neuroblastoma (13), colon (14) and ovarian cancer (15). It has been shown that As 2 O 3 regulates proliferation, invasion, differentiation, angiogenesis and apoptosis of cancer cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…hERG is overexpressed in numerous types of cancer in humans, including endometrial cancer, leukemia, melanoma and neuroblastoma, and inhibition of the hERG channel may reduce cancer cell growth and proliferation (25)(26)(27). Furthermore, this group has recently demonstrated that As 2 O 3 induces the apoptosis of MCF-7 cells through inhibition of the hERG channel (13). However, the mechanisms that regulate the expression of the hERG channel remain to be elucidated.…”
Section: A B Discussionmentioning
confidence: 99%
“…In a previous study by this group, it was identified that As 2 O 3 induces the apoptosis of MCF-7 breast cancer cells via inhibition of hERG channels (13). To date, the molecular mechanisms underlying the regulation of hERG expression in breast cancer cells remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%